Scientia Sexualis: The Forbidden Pleasures Of Flesh (2006)
The text attempts to show the appropriation of the sexuality device in Colombia during the first half of the twentieth century based on three medical documents. The relationship between a science of the sexual and the erotic manifestations of the body rev